2019
DOI: 10.3233/jnd-180342
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Fatigue in Spinal Muscular Atrophy: A Pilot Study

Abstract: Background: Fatigue is a common complaint in spinal muscular atrophy (SMA). Fatigability is well described in ambulatory SMA but the relationship to perceived fatigue has not been evaluated. Understanding this relationship has proven challenging for most disorders. Objective: To assess the relationship of perceived fatigue to fatigability, function, and quality of life in SMA. Methods: Thirty-two participants with SMA (21.9% type 2, 78.1% type 3) were recruited. Perceived fatigue and fatigability, function, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…The MFI, on the other hand, addresses the perceived physical condition in general rather than fatigue following exercise and might, therefore, be more sensitive in SMA patients (for example item 2: "Physically I feel only able to do a little" or item 14: "Physically I feel I am in a bad condition"). In accordance with previous reports regarding fatigue in general [14,21,25], physical fatigue did not correlate with disease severity or motor function in our cohort. Nevertheless, it was associated with deteriorated HRQOL as previously described for fatigue in motor neuron diseases [49], while HRQOL itself correlated positively with measures of motor function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The MFI, on the other hand, addresses the perceived physical condition in general rather than fatigue following exercise and might, therefore, be more sensitive in SMA patients (for example item 2: "Physically I feel only able to do a little" or item 14: "Physically I feel I am in a bad condition"). In accordance with previous reports regarding fatigue in general [14,21,25], physical fatigue did not correlate with disease severity or motor function in our cohort. Nevertheless, it was associated with deteriorated HRQOL as previously described for fatigue in motor neuron diseases [49], while HRQOL itself correlated positively with measures of motor function.…”
Section: Discussionsupporting
confidence: 93%
“…As fatigue is dependent on age and gender [46,47], which in part was also applicable in our cohort, prevalence estimation might be more accurate using those age-and gender-adjusted cut-off values and the estimated prevalence of 75% via MFI seems to be more precise. This is in line with the previously reported prevalence of fatigue of 81-100% in spinobulbar muscular atrophy (SBMA) and SMA patients assessed via FSS and PedsQL™ Multidimensional Fatigue Scale [24,25]. Regarding the development in fatigue over the course of 14 months, both instruments depict a similar relative change for general fatigue, which indicates their suitability to measure the same construct in the long term.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Three of the 19 studies found an association between less severe physical limitations, for example ambulation, and more emotional distress [105,111,113]. Perceptions of fatigue were universal and not associated with physical function, health related quality of life or fatigability in another study [115]. For adults with poorer physical function, engagement with a patients' association was associated with greater psychosocial wellbeing [114].…”
Section: Psychosocial Wellbeingmentioning
confidence: 96%
“…The observation that fatigue did not worsen with prolonged nusinersen treatment provides encouraging evidence that this therapy offers sustained benefit to older patients with SMA. Patient‐reported fatigue is extremely common (if not universal) for patients with SMA, so this measure is highly relevant to patients as an outcome measure.…”
mentioning
confidence: 99%